Sinorhizobium meliloti, a Slow-Growing Bacterium, Exhibits Growth Rate Dependence of Cell Size under Nutrient Limitation - Xiongfeng Dai (American Society for Microbiology, 2018)
ABSTRACT Bacterial cells need to coordinate the cell cycle with biomass growth to maintain cell size homeostasis. For fast-growing bacterial species like Escherichia coli and Bacillus subtilis, it is well-known that cell size exhibits a strong dependence on the growth rate under different nutrient conditions (known as the nutrient growth law). However, cell size changes little with slow growth (doubling time of >90 min) for E. coli, posing the interesting question of whether slow-growing bacteria species also observe the nutrient growth law. Here, we quantitatively characterize the cell size and cell cycle parameter of a slow-growing bacterium, Sinorhizobium meliloti, at different nutrient conditions. We find that S. meliloti exhibits a threefold change in its cell size when its doubling time varies from 2 h to 6 h. Moreover, the progression rate of its cell cycle is much longer than that of E. coli, suggesting a delicate coordination between the cell cycle progression rate and the biomass growth rate. Our study shows that the nutrient growth law holds robustly regardless of the growth capacity of the bacterial species, generalizing its applicability among the bacterial kingdom. IMPORTANCE The dependence of cell size on growth rate is a fundamental principle in the field of bacterial cell size regulation. Previous studies of cell size regulation mainly focus on fast-growing bacterial species such as Escherichia coli and Bacillus subtilis. We find here that Sinorhizobium meliloti, a slow-growing bacterium, exhibits a remarkable growth rate-dependent cell size pattern under nutrient limitation, generalizing the applicability of the empirical nutrient growth law of cell size. Moreover, S. meliloti exhibits a much slower speed of cell cycle progression than E. coli does, suggesting a delicate coordination between the cell cycle progression rate and the biomass growth rate.